2013
DOI: 10.1111/zph.12081
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Spread of Salmonella enterica Serovar Infantis in Serbia: Acquisition of Mutations in the Topoisomerase Genes gyrA and parC Leads to Increased Resistance to Fluoroquinolones

Abstract: Quinolone-resistant Salmonella Infantis (n = 64) isolated from human stool samples, food and poultry during the years 2006-2011 were analysed for their resistance phenotypes, macrorestriction patterns and molecular mechanisms of decreased susceptibility to fluoroquinolones. Minimum inhibitory concentrations (MICs) of nalidixic acid (NAL) and ciprofloxacin (CIP) were determined by the agar dilution procedure, and the susceptibility to additional antimicrobial agents was determined by the disc diffusion method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
3
22
0
2
Order By: Relevance
“…The fluoroquinolone-resistant Salmonella serotype has been reported worldwide 2,3,12,13,18) . However, the fluoroquinolone-resistant strain of S. Infantis found in Serbia exhibited high clonality 18) . Moreover, in Japan, fluoroquinoloneresistant strains of Salmonella in food-producing animals rarely emerged 2,3) .…”
Section: Resultsmentioning
confidence: 99%
“…The fluoroquinolone-resistant Salmonella serotype has been reported worldwide 2,3,12,13,18) . However, the fluoroquinolone-resistant strain of S. Infantis found in Serbia exhibited high clonality 18) . Moreover, in Japan, fluoroquinoloneresistant strains of Salmonella in food-producing animals rarely emerged 2,3) .…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Monitoring of resistance in S. Infantis is very important due to the frequent occurrence of this serotype that is mainly derived from poultry. According to research Velhner et al 21 PFGE analysis showed that in Serbia S. Infantis isolates have similar genetic profile indicating a clonal spread of resistance. 21 The problem with resistance in the strain of S. Typhimurium is serious because of the emergence of multiresistant strains of S. Typhimurium DT104, DT204, DT193 etc.…”
Section: Resultsmentioning
confidence: 99%
“…In another investigation in Serbia, 25% Salmonella isolated from pigs carcasses have shown resistance to amoxicillin and sulfamethoxazole [22]. There are also data about the clonal spread of S. Infantis in Serbia where mutations in the topoisomerase genes the gyrA and parC lead to increased resistance to fluoroquinolones [23]. The antibiotic resistance patterns in Salmonella isolates from food producing animals in Austria have shown that 42% of isolates were resistant to fluoroquinolones, 33% to tetracycline, 27% to streptomycin and 17% to ampicillin [24].…”
Section: Discussionmentioning
confidence: 99%